Lexical syntactic stylistic devices ("Conference on Universal Science Research 2023", 2023)
This article gives information about Lexical syntactic stylistic devices. In this article it has several paragraphs, which give full data about this. It is based on what is lexical-syntactic stylistic devices. In short, lexical-syntactic stylistic devices include climax, antithesis, litotes, simile, periphrasis, ellipses.  What is  lexical syntactic stylistic devices? What is simile? What is the difference between litotes and ellipses? In this article, candidates can learn how to be a good learner and what is lexical syntactic stylistic devices. And candidates can learn how to use it?